Penatalaksanaan Holistik Pada Ibu Rumah Tangga Usia 52 Tahun Dengan Dermatitis Kontak Iritan Melalui Pendekatan Kedokteran Keluarga Di Puskesmas Kalirejo - Dita Rifzian, Malyca Rachmaniar; Angraini, Dian Isti (CV. Jasa Sukses Abadi, 2024)
Irritant contact dermatitis (ICD) is an inflammatory skin disease caused by irritant materials or substances and can be found in everyone from all age groups, races, and genders. The definitive management is to find and avoid the cause (irritants). Applying a holistic and comprehensive family doctor approach in detecting risk factors, clinical problems, and patient management based on evidence based medicine through family-approached, patient-centered, and community-oriented. This is a case report study, which the primary data were obtained through anamnesis, physical examination, home visits. The secondary data were obtained through patient’s medical records. Mrs. P, 52 years old, presents redness and itchy spots on both soles of the feet and peeled skin since two weeks ago. The patient is worried that the complaints may interfere her daily activities. The patient is a housewife who has just replaced the bathroom floor cleaning fluid. Patient was diagnosed with ICD based on history and physical examination. The intervention results were patient complaints’ were reduced, knowledge of patients and her family regarding ICD increased, and some behaviours of the patients and family changed.